A experiência de liberdade assistida comunitária na percepção de seus operadores - Passamani, Maria Emília (2006)
This paper aims to know the perception that the operators of The Attended Freedom social-educative measure have regarding their Program. This study began from the estimated idea that the Communitarian Program of Attended Freedom House Rising Sun is successful at the accompaniment of adolescents in conflict with the law. That happens because it takes care of offenders adolescents without arresting them, preserving their living with their families and in their communities, as it is established by the Brazilian Children and Adolescents Statute. This paper identifies the activities developed by the institution regarding the attendance to the offenders adolescents, who are submitted to the Attended Freedom social-educative measures. It presents all the adolescents profiles who were helped by the Program in the following categories: number of taken care adolescents, age, gender, education level, infraction they committed, familiar income, use of drugs, kind of drug that were used, work, relapsed infraction. It identifies the aspects that make the accompaniment process easier in the institution House Rising Sun and the main impediments that hinder the implementation process of the Attended Freedom measure. The collected numbers and information were studied by the Speech Analysis method, for being the most adjusted one to achieve the research aims. The operators perceptions of the of Attended Freedom social-educative measure will be presented from some aspects that were considered more important during the interviews, as motivation, negative and positive aspects, the services nets, partnerships, the accounts rendering, its role in the Social Politics scene and the adolescents concepts, adolescents in conflict with the law, pedagogical proposal, emancipation, resocialization and youth protagonism.